Salicylic acid and thiourea mitigate salinity and drought stress in wheat (Triticum aestivum) - YADAV, TARAMANI; YADAV, GAJENDER; KUMAR, ASHWANI; KUMAR, DINESH; YADAV, RK (The Indian Journal of Agricultural Sciences, 2022)
Water and salinity stresses are the major environmental concerns limiting crop production, particularly in arid and semi-arid ecologies. Focused research is required to develop mitigating strategies to manage such stresses. Application of plant-bioregulators (PBRs) may be an effective option to manage water and salinity stresses. Therefore, a field experiment was conducted during 2016–17 and 2017–18 at semi-arid saline site of NW (north-western) India to assess the effectiveness of salicylic acid and thiourea in easing out the adverse effect of variable water deficit and irrigation water salinity regimes. Increasing water deficit and its salinity significantly (P